2019
DOI: 10.17977/jptpp.v4i1.11827
|View full text |Cite
|
Sign up to set email alerts
|

Buku Ajar Tematik Berbasis Muatan Lokal untuk Kelas IV Sekolah Dasar

Abstract: <pre><strong>Abstract:</strong> The purpose of this development research is to produce textbooks based on local content in Kabupaten Tulungagung for grade IV Primary School. Textbooks based on local content can be used as one learning resource in learning. The textbook product is developed based on the steps of the 4-D development model. Validation and test results that have been done, obtained data that is (a) the validation of the student's book reached a percentage of 85.34% with criteria … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 4 publications
0
1
0
1
Order By: Relevance
“…Guru juga harus tepat dan selektif dalam menggunakan sumber belajar yang digunakan dalam pembelajaran. Guru juga dapat memanfaatkan media maupun model pembelajaran sesuai dengan materi agar siswa tertari serta antusias dalam kegiatan pembelajaran [2]. Buku ajar juga harus menyajikan materi yang disesuaikan dengan lingkungan terdekat peserta didik dan menyajikan hubungan berbagai peristiwa sebagai satu kesatuan yang utuh sesuai dengan prinsip pembelajaran tematik yang mengaitkan konsep-konsep dari beberapa mata pelajaran dengan tema sebagai pemersatu [3].…”
Section: Pendahuluanunclassified
See 1 more Smart Citation
“…Guru juga harus tepat dan selektif dalam menggunakan sumber belajar yang digunakan dalam pembelajaran. Guru juga dapat memanfaatkan media maupun model pembelajaran sesuai dengan materi agar siswa tertari serta antusias dalam kegiatan pembelajaran [2]. Buku ajar juga harus menyajikan materi yang disesuaikan dengan lingkungan terdekat peserta didik dan menyajikan hubungan berbagai peristiwa sebagai satu kesatuan yang utuh sesuai dengan prinsip pembelajaran tematik yang mengaitkan konsep-konsep dari beberapa mata pelajaran dengan tema sebagai pemersatu [3].…”
Section: Pendahuluanunclassified
“…The results showed that (1) The application of thematic textbooks at SD YKPP had been going well by adjusting the conditions of students and schools. (2) The obstacle faced in implementing the thematic textbooks for the Kurikulum 2013 at the SD YKPP is the adjustment of the differences in the learning abilities of each student. (3) Thematic textbooks are considered to have been effectively implemented in the SD YKPP, supported by some evidence that the facilities and infrastructure at the SDYKPP are adequate, there is an increase in overall student achievement every semester, and the achievement of the objectives of the Kurikulum 2013.…”
mentioning
confidence: 99%
“…Pemanfaatan wisata Api Abadi Mrapen sebagai warisan budaya yang kemudian berdampak pada pembelajaran sejarah sebagai sumber belajar. Sumber belajar berguna bagi siswa untuk meningkatkan produktivitas belajarnya (Irwandi & Fajeriadi, 2020;Segoro et al, 2019). Sumber belajar seluas mungkin untuk kebutuhan belajar dan dalam upaya untuk mendapat hasil belajar yang maksimal (Supriadi, 2017).…”
Section: Pembahasanunclassified